2005
DOI: 10.1080/02699050500110314
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards survivors of brain injury

Abstract: Religious, economic and gender-based divisions in society affect attitudes towards survivors of brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Moreover, several studies revealed erroneous beliefs about survivors of TBI themselves (eg, as aggressive or dependent), which may increase stigmatization or stereotyping of affected individuals. [25][26][27] Thus, it is critical to also assess the knowledge held by the individuals closest to the survivor of TBI, such as friends and family members.…”
Section: Mild Traumatic Brain Injury Knowledgementioning
confidence: 99%
“…Moreover, several studies revealed erroneous beliefs about survivors of TBI themselves (eg, as aggressive or dependent), which may increase stigmatization or stereotyping of affected individuals. [25][26][27] Thus, it is critical to also assess the knowledge held by the individuals closest to the survivor of TBI, such as friends and family members.…”
Section: Mild Traumatic Brain Injury Knowledgementioning
confidence: 99%
“…The disabilities or dysfunctions associated with TBI may not be the only concerns of TBI patients. TBI patients may experience certain psychosocial problems, which have less to do with the severity of the injury but perhaps more so to do with societal perceptions [ 47 ]. These societal perceptions or stigma may also have major implications for TBI patients' rehabilitation.…”
Section: Cultural Implications Of Tbi In the Local Hong Kong Contementioning
confidence: 99%
“…More than 70% of respondents were unable to recognize that one head injury places an individual at greater risk for sustaining a second. Perhaps more importantly, however, this article sparked interest in the knowledge, expectations, and beliefs about TBI, with an increasing number of publications in this area that examine the impact of various demographic variables on TBI knowledge (ie, age [2][3][4], gender [2,3,5], ethnicity [6], education [2,3,[6][7][8], and previous personal experience with brain injury (see Appendix) [1][2][3][4]9]).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various specific TBI-related misconceptions have been identified in the literature [2][3][4][5][6][7][8][9] (for examples, see Table 1). However, the underlying factors contributing to the development and maintenance of these misconceptions, and their impact on injury outcomes and quality of life for survivors of TBI, are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation